Larvicidal Activity of 96% Ethanol Extract of Arabica Coffee Fruit Peel (Coffea arabica L.) on Mortality of Housefly Larvae (Musca domestica) - Lenggar, Benta; Unida, Tazkiah; Putra, Ichsan Luqmana Indra (Universitas Ahmad Dahlan, 2023)
Houseflies (M. domestica) are vectors of disease in humans and animals, so vegetable insecticides are needed that can be used to control M. domestica populations, one of which is Arabica coffee fruit peel extract. The purpose of this study was to determine the effect of giving various concentrations of 96% ethanol extract of Arabica coffee fruit peel on the mortality of M. domestica larvae, as well as calculating the LC50 and LT50 values of M. domestica larval mortality. The research design was a completely randomized design (CRD) using 20 third instar larvae of M. domestica. The concentration variations of Arabica coffee fruit peel extract tested were 0.05%, 0.1%, 0.5%, 1% and 0% as control with 3 replicates using the feeding assay method. Larval mortality was observed for 48 hours (hour 0, 4, 8, 12, 16, 20, 24, 28, 32, 36, 40, 44, and 48) post extract. Data were analyzed by descriptive and inferential analysis using Kruskal-Wallis test and probit analysis of LC50 and LT50. The results showed a significance value >0.05, meaning that there was no significant difference in the mortality of third instar larvae of M. domestica between treatments. The LC50 value obtained was 0.01%. LT50 values at concentrations of 0.05%, 0.1%, 0.5%, and 1% were 274.52 hours, 134.90 hours, 532.20 hours and 0 hours, respectively. The conclusion of this study is that 96% ethanol extract of Arabica coffee fruit peel has no effect on the mortality of M. domestica larvae, the concentration of Arabica coffee fruit peel extract that causes the fastest death of M. domestica larvae is 0.1%, and LT50 at extract concentrations of 0.05%, 0.1%, 0.5% is 274.52 hours, 134.90 hours, and 532.20 hours, at 0% and 1% concentrations have no LT50 value.